Tissue Polypeptide Specific Antigen as a Marker Used to Determine the Liver Diseases - Paul, D; Biswas, R; Habib, S H (Kathmandu University Medical Journal, 2012)
Background Tissue polypeptide specific antigen and its specific M3 epitope are increased in malignant as well as in some benign diseases. The level of tissue polypeptide specific antigen in serum is related mostly to proliferation capacity rather than tumor mass and cell necrosis. Objective The aim of this study was to evaluate the levels of tissue polypeptide specific antigen and other tumor markers in patients with liver cirrhosis, chronic active hepatitis and hepatoma to determine if tissue polypeptide specific antigen is important to other tumor markers in hepatoma patients. Methods Ninty-seven patients and 30 controls were included in the study. The patients were divided into three subgroups as cirrhosis, hepatoma and chronic active hepatitis. The levels of tissue polypeptide specific antigen, carcinoembryonic antigen, CA19.9, alpha-fetoprotein and transaminases were determined in all patients. Results Tissue polypeptide specific antigen levels were significantly higher in all patients than in the control group (p<0.005) According to Kruskal-Wallis test with regard to subgroups, the differences in mean values of tissue polypeptide specific antigen and alpha-fetoprotein were significant (p<0.0001 for both). There was a low correlation between tissue polypeptide specific antigen and alpha-fetoprotein in the cirrhotic and hepatoma groups, but these were significantly correlated in the chronic active hepatitis group. The correlation coefficient between tissue polypeptide specific antigen and transaminases in all patients was low. Conclusions Tissue polypeptide specific antigen is efficient for determining primary hepatoma patients and also that this marker is specific for proliferation of cells. http://dx.doi.org/10.3126/kumj.v9i1.6257 Kathmandu Univ Med J 2011;9(1):24-7